Cinnamon roll murder [large type] - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2012)
When the keyboard player for the Cinnamon Roll Six jazz band is murdered after a tour bus accident on the way to Lake Eden, Minnesota, Hannah Swensen investigates and comes up with several local suspects.